First report of brittle stars (Echinodermata: Ophiuroidea) from a seamount in the eastern Arabian Sea - U., Abdul Jaleel K.; Parameswaran, Usha V.; Biju, Anagha; S., Parthasarathi; Abdulaziz, Anas (Zootaxa, 2023)
This paper reports two species—Ophiozonella molesta (Koehler, 1904) and Ophiothamnus venustus Matsumoto, 1915, from a seamount in the Eastern Arabian Sea. This forms the first ever report of Ophiothamnus venustus from the Indian Ocean, and the first verified report of Ophiozonella molesta from Indian waters. This is the first ever work to document benthic invertebrates from seamounts in the Arabian Sea.